2003
DOI: 10.1128/aem.69.8.4777-4787.2003
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Genome-Wide Expression Analysis Identifies a Strong Ergosterol and Oxidative Stress Response during the Initial Stages of an Industrial Lager Fermentation

Abstract: Genome-wide expression analysis of an industrial strain of Saccharomyces cerevisiae during the initial stages of an industrial lager fermentation identified a strong response from genes involved in the biosynthesis of ergosterol and oxidative stress protection. The induction of the ERG genes was confirmed by Northern analysis and was found to be complemented by a rapid accumulation of ergosterol over the initial 6-h fermentation period. From a test of the metabolic activity of deletion mutants in the ergostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 72 publications
5
71
0
1
Order By: Relevance
“…In this work, the level of zymolectins on the cell wall appears to be more or less constant during the fermentation. This finding (of constant zymolectin level) is supported by work of Higgins et al 13 and Olesen et al 25 who noted no change in FLO1 expression during fermentation of two lager strains. Interestingly, no up-regulation or down-regulation was noted of CWP1 or CWP2 genes in these studies 13,25 .…”
Section: Evaluation Of Yeast Flocculence During Fermentationsupporting
confidence: 76%
“…In this work, the level of zymolectins on the cell wall appears to be more or less constant during the fermentation. This finding (of constant zymolectin level) is supported by work of Higgins et al 13 and Olesen et al 25 who noted no change in FLO1 expression during fermentation of two lager strains. Interestingly, no up-regulation or down-regulation was noted of CWP1 or CWP2 genes in these studies 13,25 .…”
Section: Evaluation Of Yeast Flocculence During Fermentationsupporting
confidence: 76%
“…Another significant outcome of this study is a clear demonstration that transcriptional responses during brewery fermentation are not necessarily comparable with the results of small-scale fermentations. Indeed, an increase in the transcription of HXT2 was observed in this study while a 50-fold downregulation was observed in another (Higgins et al, 2003a). Likewise, an increase in the transcription of many glycolytic genes was observed as the full-scale fermentation progressed, whereas a general decrease in transcription of these genes occurred during small-scale fermentation (James et al, 2003).…”
Section: Discussionsupporting
confidence: 45%
“…The high expression of HXT4, regardless of the mode of regulation, suggests that the protein encoded by this gene has an important role in hexose transport during early fermentation and that hexose transport during this period is not solely conducted by the product of HXT1, as suggested for oenological fermentations (Perez et al, 2005). While few transcription profiles for genes encoding members of this superfamily of transporters are available, Higgins et al (2003a) have reported a 50-fold downregulation in the transcription of HXT2 during a small-scale wort fermentation, which is inconsistent with the biochemical properties of the high affinity Hxt2p transporter. James et al (2003) have also reported the induction of 18 transporterencoding genes 3 days into a small-scale wort fermentation, of which seven were still highly expressed after 8 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations